SOSIALISASI PENERAPAN TERAPI SLEEP HYGIENE PADA ANAK USIA PRASEKOLAH YANG MENGALAMI GANGGUAN POLA TIDUR SAAT HOSPITALISASI DI RUANG SALMANAL-FARISI RSU ASRI PURWAKARTA - Wirdan Fauzi Rahman; Yuli Erlina; Susanti Adiningrum (Bajang Institute, 2025)
Sleep pattern disturbances are one of the problems often experienced by preschool-aged children during hospitalization. Environmental changes, loud noises, bright lights, and feelings of fear and anxiety can cause children to have difficulty falling asleep or sleeping poorly. One non-pharmacological intervention that can be done to improve sleep patterns is sleep hygiene therapy. This community service activity aims to improve the knowledge and skills of nurses in the pediatric ward of Asri Hospital, Purwakarta, in performing sleep hygiene therapy on preschool-aged children who experience sleep pattern disturbances due to hospitalization in the ward of Asri Hospital. The activity implementation method uses a lecture, demonstration, and simulation approach. The activity involved 20 participants consisting of implementing nurses and shift managers. Evaluation was carried out using pre-tests and post-tests to assess knowledge gains, as well as observation of skills during the simulation practice. The results of the activity showed an increase in participants' knowledge from an average score of 58% (pre-test) to 89% (post-test). In addition, 90% of participants were able to perform the Sleep Hygiene therapy simulation with the correct technique. Participants also showed high enthusiasm in participating in the entire series of activities. Socialization and training on sleep hygiene therapy have proven effective in improving the knowledge and skills of nurses at Asri General Hospital. Sleep hygiene therapy effectively improves sleep patterns in preschool-aged children during hospitalization by establishing a bedtime routine, creating a comfortable environment, and actively involving parents